Factors Related to Snack Consumption Behavior at SDN 1 Purwoharjo Banyuwangi - Gufron Wahyudi; Elisa Yulistiya; Widya Rizki Septianingtyas (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2021)
This thesis discusses the behavior of elementary school student snacks consumption. Based on the facts in the field shows that 78% of children consume snacks in the school environment (BPOM, 2008). Food snacks that contain fat, energy, and high salt must be limited, because it can provide excessive energy intake, resulting in an increase in the risk of over nutrition that causes one of the triggers for degenerative diseases such as stroke, diabetes mellitus, coronary heart disease and so forth. Besides consuming foods that are not good hygiene level can cause interference with the digestive tract, for example typhus, mutah, nausea, diarrhea and so forth (Yuliastuti, 2012)Therefore this study discusses the description of the behavior of consumption of snacks and factors related to the behavior of consumption of snacks.The design of this study was cross sectional. The population in this study was all students in grades IV, V, and VI at SDN I Purwoharjo with a sample of 72 students. The sampling method used is simple random sampling. The instrument used was a questionnaire.This study uses the Spearman Rank test. Based on the results of the R test sig. R count 0,000 < 0.05, i.e. there is a relationship between variable student characteristics (including gender, knowledge), allowance, parental characteristics (including parental education, parents' occupation) with snack consumption behavior.From this research it is expected to provide information and increase students' knowledge, to choose and consume snacks properly and correctly. Keywords: children school, snack, snacks consumption behavior.